Mental health treatments in an Italian prison: the Parma integrated approach - L. Pelizza; D. Maestri; G. Paulillo; P. Pellegrini (European Psychiatry, 2022)
Introduction Mental health interventions for Italian (and European) prisoners with mental disorders remain a problematic issue, despite radical changes in general psychiatric care and a 2008 major government reform transferring mental health care in prison to the National Health Service. Indeed, according to the American Psychological Association, 64% of incarcerated individuals report mental health concerns.